Penggunaan Tuturan Tidak Langsung pada Anak Usia 3 Tahun : Sebuah Kajian Pragmatik - Tri Pujiati; Meria Zakiyah Alfisuma (Journal of Social, Culture, and Language, 2023)
Three-year-old children have the ability to use speech in the form of indirect speech as an effort to convey their intentions or desires to others. This research was conducted in an effort to see the pragmatic abilities possessed by 3-year-old children. A pragmatic approach with a qualitative descriptive research method is used to analyze the pragmatic abilities of 3-year-old children. Data collection techniques are carried out using recording techniques. Data was taken for one month from February to March 2023. The data in this study used a single subject in children aged 3 years. The results showed that the research subjects with a single case in children aged 3 years had good skills in using indirect speech. Indirect speech used by a single subject is done to get the wishes according to the child's expectations. Communication between parents and single subjects is also considered successful because indirect speech can be well understood by both parties, namely parents and children. Pragmatically, it can be seen that the speaker uses indirect speech to the speaker only at certain times and according to the context of the conversation so that the speaker can understand the intent conveyed by the speaker. Keywords: Indirect Speech, Pragmatics, and Communication